Bantuan Hukum Timbal Balik dalam Penanganan Kejahatan Transnasional: Studi Kasus Indonesia-Swiss - Yuwono, Teguh; Kusniati, Retno; Ardianto, Budi (Faculty of Law, Universitas Jambi, 2021)
Transnational crime is a cross-border crime that has troubled many states. In enforcing the criminal law of a states, sometimes it is difficult for the state to pursue transnational criminals because of its cross-border nature, so that the differences in jurisdiction between countries make it difficult to enforce the law. For this reason, in order not to be hindered by the cross-border nature, the states concerned can cooperate between states using the Mutual Legal assistance Agreement. Mutual Legal Assistance is an international legal instrument that is widely used by countries as a tool to take action and prevent crimes that are transnational in nature. With this agreement, more effective law enforcement can be carried out and make it easier for law enforcers to move into areas with different jurisdictions. This research is a normative juridical research based on secondary data with a statutory approach. This article concludes that mutual legal assistance will greatly play a role in law enforcement on transnational crimes involving Indonesia-Switzerland